Milk yield characteristics of karakaş-akkaraman ewes in extensive conditions - Orhan Yılmaz; Hüseyin Denk; Mikail Arslan (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate milk yield characteristics ol Karakaş- Akkaraman ewes in extensive conditions. The study has been conducted on 70 Karakaş-Akkaraman ewes in Edremit. Van . Lactation milk yield, lactation milk fat percentage and lactation length in Karakaş-Akkaraman ewes were 50.50 kg. 6.60 % and 144.90 days, respectively. The effects of birth type and age on lactation milk yield were significant (P<0.05, P<0.001). but the effect of live weights of ewes at the initiation ol lactation was not significant, the effect of age on lactation length was significant (P<0.01), but the effects ol birth type and live weights of ewes at the initiation of lactation were not significant furthermore, the effects of birth type, age and live weights of ewes at the initiation of lactation on lactation milk lat percentage were not significant. The le-notypic correlation coefficient between lactation milk yield and lactation length which was found 0.90 (P<0,001), the le-notypic correlation coefficient between lactation milk yield and lactation milk fat percentage which was found - 0 46 (p<0.001).